(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
Analysis of the practice of the Constitutional Court of Montenegro in the last few years shows an evident increase in the number of cases in which the applicant is asking for an assessment of the compatibility of national legislative acts with the Constitution of Montenegro, asking for annulment because of alleged incompatibility with a certain EU directive. Therefore, this article discusses one of the most interesting questions which countries in the process of the accession to the European Union are facing – the status of the sources of EU law in the legal system of candidate countries before they become members of the European Union. In this context, the authors will examine the case law of the Constitutional Court of Montenegro related to situations where the Montenegrin legislator has transposed a directive into the domestic legal order. After comparative analysis, the article will shed more light on the subject stances and will discuss possible solutions depending on the facts of the case when the principle of the direct application of directives can be established.